2007
DOI: 10.1007/s12119-007-9000-z
|View full text |Cite
|
Sign up to set email alerts
|

“To Protect and to Serve?”: An Exploration of Police Conduct in Relation to the Gay, Lesbian, Bisexual, and Transgender Community

Abstract: While there are studies that focus specifically on hate crimes, especially anti-lesbian, gay, bisexual, and/or transgender motivated violence, little research has been done to examine the role that law enforcement officials play in responding to crimes related to the Gay/Lesbian/Bisexual/Transgender (GLBT) community. This study, therefore, attempts to do just that. Using traditional content-analysis techniques, we examine 1,896 incident reports that were collected by a GLBT advocacy group in Minnesota, between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 19 publications
5
54
0
Order By: Relevance
“…This finding has broad relevance since past research shows that police agencies in the USA have been criticised for identity-relevant policing of minority groups that has typically resulted in transgender people being treated in an unfair manner (See Alliance for a Safe & Diverse DC, 2008;Berman & Robinson, 2010;Edelman, 2014;Grant et al, 2011;Heidenreich, 2011;Herek & Berrill, 1992;Miles-Johnson, 2013b;Redfern, 2014;Wolff & Cokely, 2007, Woods et al, 2013. It also clearly shows that any potential contact between the police and transgender people would more than likely be This idea is supported by Milner (1996) who also concluded that SIT could offer a clear explanation regarding why many minority groups (such as the transgender community)…”
Section: "…When One Of 'Them'… You Know… a Gay Male Or A Tranny Comesmentioning
confidence: 98%
See 3 more Smart Citations
“…This finding has broad relevance since past research shows that police agencies in the USA have been criticised for identity-relevant policing of minority groups that has typically resulted in transgender people being treated in an unfair manner (See Alliance for a Safe & Diverse DC, 2008;Berman & Robinson, 2010;Edelman, 2014;Grant et al, 2011;Heidenreich, 2011;Herek & Berrill, 1992;Miles-Johnson, 2013b;Redfern, 2014;Wolff & Cokely, 2007, Woods et al, 2013. It also clearly shows that any potential contact between the police and transgender people would more than likely be This idea is supported by Milner (1996) who also concluded that SIT could offer a clear explanation regarding why many minority groups (such as the transgender community)…”
Section: "…When One Of 'Them'… You Know… a Gay Male Or A Tranny Comesmentioning
confidence: 98%
“…Throughout the 1990s, increased attention to crimes and harassment of the LGBT community resulted in many US police organisations implementing training programs for police officers to respond appropriately. However critics argued that few police training programs in the US offered specialised training modules that sensitised police officers to these types of crimes (Sloan, King & Sheppard, 1998), and although many states participated in this type of training (for example, Alabama, Arizona, California, Florida, Michigan, New York, Texas, and West Virginia) less than half of the programs mentioned sexual orientation in the training (Sloan et al, 1998) or gender diversity (Wolff & Cokely, 2007). More recently, multiple police agencies in cities such as Washington D.C., New York City and San Francisco have trimmed policing programs tailored to suit specific community needs (such as liaison units created to respond to specialty calls from members of the transgender community) (Bagby , 2012;Israel, Harkness, Delucio, Ledbetter and Avellar, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, Amnesty International (2005: 3) concludes in a report on police brutality against lesbian, gay, bisexual, and transgender (LGBT) Americans that ''in the U.S., LGBT people continue to be targeted for human rights abuses by the police based on their real or perceived sexual orientation or gender identity''. Empirical studies back up these claims, suggesting, for example, that many police officers hold antigay attitudes (Bernstein and Kostelac, 2002); that many LGBT victims of hate crimes do not report their crimes to police because they fear police mistreatment (Herek et al, 2002); and that reports of police misconduct and inaction in cases involving LGBT crime victims are persistent over time (Wolff and Cokely, 2007). As such, MSM potential complainants in HSCS cases may not trust the police to take their case seriously.…”
Section: Discussionmentioning
confidence: 99%